Historical poetics: revisiting gender in Isabella bird’s polychronotopic account of Malaya - Barani, Forough; Wan Yahya, Wan Roselezam (Universiti Putra Malaysia Press, 2013)
This paper investigates the representation of time and space in Isabella Bird’s The Golden Chersonese and the Way Thither (1883), her travel narrative on Malaya, through a Bakhtinian discussion of the chronotope. The study examines the historical poetics of the text and compares the intra-textual relation between time and space, as described by Bird, with an extra-textual account of the historical cultural condition of Malaya in 1883. This paper further seeks to underline the issue of gender and its influence on the narrative. The Golden Chersonese can be seen as a portrayal of an imperial look at the land and people of Malaya; whilst the narrative thus points to the costumes and religion of the Malays, it cannot escape the influence of its narrator’s gender. Bird’s individuality as a female traveller against the background of her native land is discussed with regard to her gender. In addition, chronotopes of 1883-Malaya, with greater focus on social, cultural and religious issues, and 1883-England as an imperial power, besides the perception of gender, are also compared. Finally, by examining various chronotopic units in The Golden Chersonese, the paper concludes that Bird’s narrative is a polychronotopic text. This research fills the gap in literature regarding a Bakhtinian perspective on travel narrative writing, with reference to time and space.